MANAJEMEN SARANA PRASARANA PENDIDIKAN - ., Rosnaeni (Universitas Islam Negeri Alauddin Makassar, 2019)
Facilities and infrastructure are supporting tools for success in public services, because if these two things are not available, all activities carried out will not achieve the expected results. School facilities and infrastructure is one of the supporting factors in achieving the success of the teaching and learning process in schools. This can be achieved if adequate facilities and infrastructure are available along with optimal management. To realize and regulate this matter the government through PP No. 19 of 2005 concerning National Education Standards, article 1 paragraph (8) states that facilities and infrastructure standards are national education standards relating to learning spaces, sports venues, places of worship, libraries, laboratories, workshops, playgrounds, places for recreation and creation, decision making, giving full autonomy rights to each level of the education unit, to optimize the provision, utilization, maintenance and control of educational facilities and infrastructure. Schools are required to have independence in organizing and managing school needs according to the needs based on the aspirations and participation of school residents while still referring to the applicable national education laws and regulations.